Pharmacists’ Role in Enhancing Community Awareness of Cancer Prevention and Early Detection - Aniek S. Budiatin; Dinda MN Ratri; Anik Rahmawati; Samirah; Toetik Aryani (Jurnal FARMASIMED (JFM), 2025)
The incidence of cancer continues to increase annually, yet public awareness of early symptoms remains relatively low. A previous study in one of the sub-districts in Kenjeran showed that around 40% of housewives had never performed BSE (Breast Self-Examination) as an early detection effort for breast cancer. This study aimed to determine the effect of pharmacist-led education and demonstration on improving community knowledge and quality of life in cancer prevention and awareness efforts. This study used a pre-post test group design experimental method and was conducted on October 7, 2020, at the Kejawan Lor Futsal Field. The intervention was carried out through education and demonstration methods in three stages: preparation, implementation, and evaluation. Measurements were taken using questionnaires assessing two variables knowledge and quality of life through pre-tests and post-tests. The results show that knowledge scores increased significantly, from an average of 44% to over 86% after the intervention. Similarly, quality of life scores improved from 33–55% to 83–88% in the post-test. These findings indicate that educational approaches accompanied by demonstrations are effective in raising public knowledge and awareness about cancer prevention. This intervention also has a positive impact on improving the respondents’ quality of life. Therefore, similar programs should be continuously implemented, especially in communities with limited access to health information, such as those in the Kenjeran District.